From Fintech to Competitiveness: Financial Sustainability Performance of MSMEs in the Digital Era - Pitaloka, Diah Ayu; Afandy, Chairil (Management Analysis Journal, 2025)
The main objective of this study is to analyze the role of competitiveness as a mediator in the relationship between financial technology (fintech) adoption and financial sustainability performance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Fintech provides easy access to digital financial services that positively impact productivity and transaction efficiency in MSMEs. This study uses the Practice-Based View (PBV) approach to understand how MSMEs can adopt fintech to improve their competitiveness and financial sustainability performance. Data was collected from 190 respondents who have adopted fintech using purposive sampling and snowball sampling techniques. This research uses the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method through SmartPLS 4.0. The results showed that fintech significantly affects competitiveness and financial sustainability performance in MSMEs, and competitiveness substantially mediates the relationship between the two. This study confirms that using fintech as a strategic practice can strengthen competitiveness and thus encourage financial sustainability performance in the long term.